Penerapan Model Pembelajaran Think Pair Share Untuk Meningkatkan Hasil Belajar Siswa Materi Limit Fungsi Aljabar Di Kelas XI IIS 1 - Wulandari, Retno (Inovasi: Jurnal Diklat Keagamaan, 2023)
ABSTRACT The Think Pair Share strategy was chosen for the following reasons, including: (1) based on daily observations on previous material until this research was conducted, students in class XI IIS 1 achieved learning outcomes that were low and lack of interest in learning Mathematics due to a mindset of knowledge Mathematics is abstract, and (2) this Think-Pair-Share strategy has never been practiced and carried out either by researchers as educators or by students in class XI IIS 1. In its implementation there are a number of crucial elements that must be done so that the application of TPS can increase activeness student learning. These important things are: (1) the Thinking stage is carried out in groups. Each group consists of 2 people and holds discussions with the help of LKPD, (2) in the Pair stage it is carried out with students in groups with 4 members consisting of a combination of 2 groups in the previous stage (3) in the Share stage one of the groups in the pair stage is asked to explain the results of the group discussion in completing the LKPD in front of the class with the attention of all students in the class. The results showed that the steps of the 100% Think Pair Share (TPS) type of cooperative learning model could increase the learning activity of class XI IIS 1 MAN 1 Pasuruan students then indicators of success in cognitive and psychomotor aspects were > 80% well fulfilled.